The scale-up and integration of contraceptive service delivery into nursing school training in the Democratic Republic of the Congo. Issue 6 (2nd May 2021) - Ntabona, Alexis; Binanga, Arsene; Bapitani, Mr Désiré Josué; Bobo, Beatrice; Mukengeshayi, Bitshi; Akilimali, Pierre; Kalong, Gloria; Mujani, Zenon; Hernandez, Julie; Bertrand, Jane T
Abstract: In Kinshasa, Democratic Republic of the Congo (DRC), modern contraceptive prevalence is low by international standards: 29.6% as of 2020. A 2015 pilot study demonstrated the feasibility and acceptability of using medical and nursing students to administer DMPA-SC (the subcutaneous injection) among other methods at the community level. The more far-reaching discovery was the potential of clinically trained students to increase access to low-cost contraception in the short-run, while improving the quality of service delivery for future generations of healthcare providers. Scale-up involved integrating the family planning curriculum into the training of nursing students, including classroom instruction in contraceptive technology and service delivery, coupled with a year-long field practicum in which students offered a range of contraceptive methods during intermittent outreach events, door-to-door distribution or sales from their homes. Starting in 2015, a multi-agency team consisting of an international non-governmental organizations (NGO), several Ministry of Health directorates and a local NGO used the ExpandNet/WHO framework to guide this scale-up. This article details the nine steps in the scale-up process. It presents results on increases in contraceptive uptake, feedback from participating nursing school personnel and the employment experience of the graduates from this programme. Between 2015 and 2019, the family planning curriculum was incorporated into 30.8% of the 477 nursing schools in 7 of the 26 provinces in the DRC. Students delivered 461 769 couple-years of protection (the key output indicator for family planning programmes). Nursing school personnel were strongly favourable to the approach, although they needed continued support to adequately implement a set of additional interventions related to the service delivery components of the new training approach. Post-graduation, only 40.1% of graduates had paid employment (reflecting the staggering unemployment in the DRC); among those, over 90% used their family planning training in their work. We describe the multiple challenges faced during the scale-up process and in planning for expansion to additional schools.